ANALISIS DAN STRATEGI PENCAPAIAN PROGRAM SWASEMBADA DAGING SAPI (PSDS) TAHUN 2014 PROVINSI SULAWESI TENGAH - Gito Nugroho, Muchlish (Katalogis, 2015)
Beef Self-Sufficiency Program 2014 is one of the main programs of the Ministry of Agriculture. This program is associated to achieve food security of animal origin resource-based domestic livestock. The program is also an opportunity to be a driving force in restoring Indonesia as beef exporter in the past. Central Sulawesi Province was designated as one of twenty provincial priorities in the local cattle development in order to support the Beef Self-Sufficiency Program 2014. The research is intended to analyze the development of the objective conditions of dairy farms in the Province of Central Sulawesi, the achievement of Beef Self-Sufficiency Program 2014 in the Central Sulawesi Province, and arrange appropriate strategies in establishing Beef Self-Sufficency Program 2014 in Central Sulawesi Province.